Managerial Ownership, Financial Distress, Company Size and Tax Avoidance - Ni Luh Putu Ayu Kusumaning Dewi; Putu Ery Setiawan (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
Tax avoidance is an effort made by taxpayers to minimize their tax expense by not violating tax regulations. This study aims to determine the factors that influence tax avoidance including managerial ownership, financial distress, and firm size. This research examines property and real estate companies listed on the Indonesia Stock Exchange period 2015-2021. This study ia an associative quantitative research using multiple linear regression analysis method. The method of determining the sample using purposive sampling method and obtain a sample of 11 companies. The results of the analysis show that firm size have a significant effect on tax avoidance while managerial ownership and financial distress has no significant effect on tax avoidance. The results of this study can provide support for agency theory and positive accounting theory as well as become material for consideration for the government and companies regarding the selection of policies in the field of taxation.